2015
DOI: 10.1002/anie.201505456
|View full text |Cite
|
Sign up to set email alerts
|

Versatile and Efficient Site‐Specific Protein Functionalization by Tubulin Tyrosine Ligase

Abstract: A novel chemoenzymatic approach for simple and fast site-specific protein labeling is reported. Recombinant tubulin tyrosine ligase (TTL) was repurposed to attach various unnatural tyrosine derivatives as small bioorthogonal handles to proteins containing a short tubulin-derived recognition sequence (Tub-tag). This novel strategy enables a broad range of high-yielding and fast chemoselective C-terminal protein modifications on isolated proteins or in cell lysates for applications in biochemistry, cell biology,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 45 publications
0
77
0
4
Order By: Relevance
“…30 The docking studies of these derivatives showed that this reactivity can be traced back to three binding modes. For small substituents such as fluorine and chlorine that have a negative partial charge, the binding behavior is similar to that of tyrosine ( 4 ) and the substituent points towards the small positively charged pocket formed by arginine-202 and tryptophan-204 (ESI Fig.…”
Section: Resultsmentioning
confidence: 99%
“…30 The docking studies of these derivatives showed that this reactivity can be traced back to three binding modes. For small substituents such as fluorine and chlorine that have a negative partial charge, the binding behavior is similar to that of tyrosine ( 4 ) and the substituent points towards the small positively charged pocket formed by arginine-202 and tryptophan-204 (ESI Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Ligases have also been exploited to add new functionality to mAbs. These include Sortase, tubulin tyrosine ligase, and spyligase . In each case a specific peptide sequence is added to the C‐terminus of the light and/or heavy chains of the mAb.…”
Section: Resultsmentioning
confidence: 99%
“…Popular approaches to achieve this goal include chemo‐enzymatic tag‐based functionalization methods that combine enzyme‐specific protein tags and labeling probes that are enzymatically transferred to the appropriate tag . Examples of these strategies include biotin ligase (BirA), spy ligase, formylglycine‐generating enzyme (FGE), sortase A (SrtA), transglutaminase, phosphopantetheinyl transferases Sfp and AcpS, and tubulin tyrosine ligase . However, the specificities of the exploited enzymes for their corresponding recognition tags are often accompanied by a rather narrow tolerance for suitably derivatized labeling probes.…”
Section: Methodsmentioning
confidence: 99%